The Effect of Mulligan Mobilization Technique on Static and Dynamic Balance in Patients with Moderate to Severe Knee Osteoarthritis: A Randomized Controlled Clinical Trial - Javid Mostamand; Maryam Adeli; Hosseinali Ahmadi; Akbar Hassanzadeh (Shiraz University of Medical Sciences, 2023)
Background: Knee osteoarthritis is the most degenerative joint disease and can consequently cause a defect in balance control. Controlling balance is necessary to prevent physical and psychological damage. The current study investigated the effects of the Mulligan mobilization technique on static and dynamic balances in patients with moderate to severe knee osteoarthritis. Methods: In a randomized controlled clinical trial, 31 patients with moderate to severe knee osteoarthritis were selected and then randomly assigned to two groups of treatment (16 patients) and control (15 patients). Static and dynamic balances and pain score were evaluated in these patients once before and once after 10 sessions of treatment. Independent and paired t-tests were used for statistical analysis. The level of statistical significance was set at p<0.05. Results: Pain decreased significantly in both groups after intervention (p<0.001). The treatment group experienced significantly greater reduction in pain than the control group (p=0.005). A significant improvement was found in both static (p=0.01) and dynamic (p=0.006) balance in the treatment group after the intervention. Additionally, the improvement in static (p=0.04) and dynamic (p=0.02) balance was greater in the treatment group compared to the control group. Conclusions: The results of the present study reveal that Mulligan mobilization technique can improve balance in patients with moderate and severe knee osteoarthritis.